2020
DOI: 10.1038/s41598-020-69196-4
|View full text |Cite
|
Sign up to set email alerts
|

Roles of sarcoplasmic reticulum Ca2+ ATPase pump in the impairments of lymphatic contractile activity in a metabolic syndrome rat model

Abstract: the intrinsic lymphatic contractile activity is necessary for proper lymph transport. Mesenteric lymphatic vessels from high-fructose diet-induced metabolic syndrome (MetSyn) rats exhibited impairments in its intrinsic phasic contractile activity; however, the molecular mechanisms responsible for the weaker lymphatic pumping activity in MetSyn conditions are unknown. Several metabolic disease models have shown that dysregulation of sarcoplasmic reticulum ca 2+ Atpase (SeRcA) pump is one of the key determinants… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 82 publications
1
12
0
Order By: Relevance
“…While TRPM4 has yet to be identified in LMCs, investigations into IRAG modulating IP3-mediated calcium releases in LMCs is warranted, particularly as it pertains to activation of Ano1 and regulation of lymphatic contraction frequency. Lastly, the SR store refilling by SERCA in LMCs ( Lee et al, 2020 ) and the calcium sources utilized to refill the store remain underappreciated in lymphatic muscle. Questions remain as to whether the components of the store operated calcium entry, Stim and Orai, are expressed and if they are functional as would be expected for calcium homeostatic control with frequent SR calcium release ( Emrich et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…While TRPM4 has yet to be identified in LMCs, investigations into IRAG modulating IP3-mediated calcium releases in LMCs is warranted, particularly as it pertains to activation of Ano1 and regulation of lymphatic contraction frequency. Lastly, the SR store refilling by SERCA in LMCs ( Lee et al, 2020 ) and the calcium sources utilized to refill the store remain underappreciated in lymphatic muscle. Questions remain as to whether the components of the store operated calcium entry, Stim and Orai, are expressed and if they are functional as would be expected for calcium homeostatic control with frequent SR calcium release ( Emrich et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…We also found that insulin-resistant LMCs showed decreased endoplasmic reticulum calcium content without affecting non-sarcoplasmic reticulum Ca 2+ ATPase (SERCA)-mediated calcium uptake. Inhibition of SERCA by the irreversible SERCA inhibitor, thapsigargin, in lymphatic vessels diminished both phasic contractile frequency and amplitude without affecting the tone ( Lee et al, 2020 ). There are three distinct genes encoding SERCA pumps, SERCA 1, 2, and 3 resulting in more than 10 SERCA isoforms expressed in various muscles and non-muscle cells ( Hovnanian, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…VO 2 in the obese group) [40]. Furthermore, the activity of SERCA was shown to be impaired in animal models of obesity and metabolic syndrome [41,42], potentially representing an adjunctive factor accounting for the poorer response to PBC-induced thermogenesis in the group of obese-women. Thereby, dysmetabolism in obesity could possibly affect muscle substrate oxidation [43], de facto preventing a prompt thermogenic response to cold exposure.…”
mentioning
confidence: 99%